The Effect of Education and Teaching Experience on the Professionalism of Elementary School Teachers - Marwati Marwati; Sri Langgeng Ratnasari; Jaya Dwi Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to analyze the effect of education and teaching experience on the professionalism of teachers at State Elementary Schools. The study used a mixed methods approach with an explanatory sequential design. The first stage was conducted using a quantitative survey approach, involving 68 elementary school teachers as research respondents. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability, and were then analyzed using multiple linear regression. The second stage was conducted through qualitative elaboration using limited interviews to explain and strengthen the quantitative findings. The results of the study showed that education and teaching experience simultaneously had a significant effect on teacher professionalism. Partially, education had a positive and significant effect on teacher professionalism, and teaching experience also had a positive and significant effect, with a more dominant contribution. The qualitative findings strengthened the quantitative results by showing that formal education provides a foundation for pedagogical and professional competence, while teaching experience shapes professional maturity, classroom management skills, and reflection on teaching practices. This study concludes that improving the professionalism of State Elementary School teachers requires relevant educational qualifications and adequate teaching experience as part of a process of continuous professional learning